Objective and specific tracking of anhedonia via event-related potentials in individuals with cocaine use disorders. (1st July 2016) - Parvaz, Muhammad A.; Gabbay, Vilma; Malaker, Pias; Goldstein, Rita Z.
Highlights: Anhedonia is a core symptom of drug addiction but assessed only subjectively. Reward positivity (RewP) is a reward-sensitive event-related potential. RewP amplitude is correlated with anhedonia and depression severity. However, anhedonia explains a significant variance in RewP amplitude. Significantly more than demographics, drug-use, and depression. Abstract: Background: Hyposensitivity to non-drug reward, behaviorally manifested as anhedonia, is a hallmark of chronic substance use. Anhedonia is a transdiagnostic symptom underpinned by neurobiochemical disturbances in the reward circuit, yet an objective measure to assess anhedonia severity still eludes the field. We hypothesized that the Reward Positivity (RewP) component of the event-related potentials (ERPs) will specifically track anhedonia as the RewP is attributed to the same brain regions that are also implicated in anhedonia. Methods: Forty-six individuals with cocaine use disorders (iCUD) performed a gambling task predicting whether they would win or lose money on each trial, while ERP data was acquired. RewP in response to predicted win trials was extracted from the ERPs using the principal component analysis. State anhedonia and depression severity were assessed using the Cocaine Selective Severity Assessment (CSSA). Results: Although RewP amplitude correlated with both anhedonia and depression, only the RewP-anhedonia correlation survived a correction for depression severity. Further, a hierarchical multiple regression analysis revealed that anhedonia explained a significant amount of variance in the RewP amplitude, and this variance was significantly greater than that explained by demographics, severity and recency of drug use and even depression. Conclusions: These results show that RewP amplitude in response to rewarded trials tracks state anhedonia severity in iCUD. We argue that this association is perhaps driven by the activity in the dopaminergic mesocorticolimbic reward pathway that may underlie anhedonia symptomology as well as modulate RewP amplitude.